2011
DOI: 10.3348/kjr.2011.12.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Pancreatic Ductal Adenocarcinoma from Pancreatic Serous Cystadenoma, Mucinous Cystadenoma, and a Pseudocyst with Detailed Analysis of Cystic Features on CT Scans: a Preliminary Study

Abstract: ObjectiveTo determine whether or not detailed cystic feature analysis on CT scans can assist in the differential diagnosis of pancreatic ductal adenocarcinoma (PDAC) from serous cystadenoma (SCN), mucinous cystadenoma (MCN), and a pseudocyst.Materials and MethodsThis study received Institutional Review Board approval and informed patient consent was waived. Electronic radiology and pathology databases were searched to identify patients with PDAC (n = 19), SCN (n = 26), MCN (n = 20) and a pseudocyst (n = 23) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…[ 3 ] The morphologies are inconsistent, including irregular, striped, speckled, focal, sand-like calcifications, calcifications forming polycyclic structures, and so on. [ 2 , 5 , 6 , 11 , 13 , 15 , 17 , 18 , 34 , 35 ] Calcifications in pancreatic malignancies have been well described previously, [ 21 , 22 , 28 , 30 ] although there is a lack of summaries of calcifications in pancreatic tuberculosis, partly because of its rarity. Based on these reports, calcifications may be useful, but not specific imaging criteria for the differentiation of pancreatic tuberculosis from malignancy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[ 3 ] The morphologies are inconsistent, including irregular, striped, speckled, focal, sand-like calcifications, calcifications forming polycyclic structures, and so on. [ 2 , 5 , 6 , 11 , 13 , 15 , 17 , 18 , 34 , 35 ] Calcifications in pancreatic malignancies have been well described previously, [ 21 , 22 , 28 , 30 ] although there is a lack of summaries of calcifications in pancreatic tuberculosis, partly because of its rarity. Based on these reports, calcifications may be useful, but not specific imaging criteria for the differentiation of pancreatic tuberculosis from malignancy.…”
Section: Discussionmentioning
confidence: 97%
“…Based on these reports, calcifications may be useful, but not specific imaging criteria for the differentiation of pancreatic tuberculosis from malignancy. [ 3 , 6 , 7 , 15 , 17 , 21 , 22 , 28 , 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Mucinous cystadenomas are usually macrocystic (>5 cm) with a smooth contour with or without septations. [ 12 ] Calcifications if present tend to be more peripheral in nature. [ 13 14 ] They can exert mass effect over the pancreatic duct and cause duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…4,69 Accuracy of preoperative CT diagnosis has been reported to be as low as 23.3%. 3 It has been suggested that the predictive value of CT for diagnosis of pancreatic serous cystadenomas may improve with increased number of detectors, from 3.6% in CTs with less than 64 detectors to 28.7% in CTs with 64 detectors or more.…”
mentioning
confidence: 99%